Reverse total shoulder arthroplasty versus locked plate fixation for proximal humeral fractures in the elderly: a systematic review. - Janette Iking; Karen Fischhuber; J Christoph Katthagen; Sebastian Oenning; Michael J Raschke; Josef Stolberg-Stolberg; Jeanette Köppe (PLoS ONE)
Introduction For surgical treatment of proximal humeral fractures (PHF) in older patients, there is no consensus if locked plate fixation (LPF) or reverse total shoulder arthroplasty (RTSA) yields better clinical results. The purpose of this study was to systematically review the clinical and functional outcomes of LPF and RTSA. We hypothesized that RTSA would outperform LPF in patients with PHF aged 65 years or older. Materials & methods A comprehensive literature search was performed on PubMed and Google Scholar from 1 July 2022 up to 12 January 2024 by two independent reviewers. Comparative studies reporting on the functional outcome using the Constant-Murley score (CMS) in patients aged 65 years or older, treated after 2012 for PHF with LPF or RTSA and with a mean follow-up time of at least 12 months were included. Ten studies with 244 LPF and 287 RTSA patients were included into the statistical analysis. We used a frequentist network meta-analysis to assess the comparative effectiveness of the treatments. Individual risk of bias of the studies was assessed using the ROB2 and ROBINS-I tools. Results Our network meta-analysis of the CMS resulted in the following order ranked from lowest to highest: LPF, LPF +  screw augmentation, hemiarthroplasty (HA), RTSA +  cemented stem, non-surgical treatment, LPF +  fibular allograft, RTSA with an inclination angle of 135° (RTSA IA 135°), RTSA. However, none of the direct or indirect comparisons resulted in statistically noticeable differences. Conclusion In conclusion, functional superiority of either treatment method is still unknown, with even high-powered RCT not being able to detect statistically noticeable differences in terms of function. Patient-individual factors, such as bone quality, sex and age have to be included when making treatment decisions.